Influence of processing on the quality of pomaceas juice (Pyrus communis and Malus domestica) - doi: 10.4025/actasciagron.v35i1.15360 - Rocha, Andressa Schaia; Zielinski, Acácio Antonio Ferreira; Ávila, Suelen; Nogueira, Alessandro; Wosiacki, Gilvan (Acta Scientiarum. Agronomy, 2012)
Pear (Pyrus communis), which is intensively cultivated in subtropical and temperate climates, has recently attained the 3rd position in the world fruit ranking, just after apple and peach. This fruit exhibits certain similarities to apple with respect to the pulp, but pear is used as a raw material only when apple is no longer available, which suggests that the same technology line may be utilized. Both fruits do have processing compatibilities, and it is permissible to add pear juice to apple juice at levels defined by law. Quality indicators, such as pH, total acidity, total phenolic compounds and antioxidant activity were used. The simple sugar analysis clearly defines fructose as the main component in pear juice, and lower figures were found when enzymatic processing was used. Color intensity measured instrumentally was much greater in pear juice with all processing methods and in apple juice when an enzymatic method was used. The results clearly indicate proper ways of processing pear and apple, aiming to have better products, as the grinding and extraction processing steps surely affect the fruit juice quality.